Vpliv socialne stratifikacije na značilnosti športno rekreativne dejavnosti v Sloveniji - Doupona, Mojca (Šport (Ljubljana), 2010)
The theoretical introduction sheds light on the importance of the stratification factors for engaging in a sport-recreational activity. Sport-recreational activity largely depends on these factors; the most influential of them include gender, age, environment and education to which the population's socioeconomic status is related. In 1973 a longitudinal study was launched in Slovenia dealing with the sport and recreational activity of Slovenians. The article presents some results of the most recent study concerning the types and modes of sportrecreational activities in relation to socio-demographic characteristics.
Keywords: družbena razslojenost; odrasli; raziskave; rekreacija; Slovenija; šport; športna aktivnost